KOMUNIKASI INSTRUKSIONAL HIMPUNAN MAHASISWA ISLAM CABANG PEKANBARU DALAM MEMBENTUK KEPRIBADIAN KADER - Pebrizon "; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Himpunan Mahasiswa Islam (HMI) Pekanbaru is one of Himpunan Mahasiswa Islam’s branch with is located in Pekanbaru. Himpunan Mahasiswa Islam Pekanbaru has a developing process in implementation of its funchtion. The development program in HMI held in suistainable training with started in Basic Training (First Member Training). This research was intended to learn about instructional communication process, instructional communication method, instructional communication tool, and communication issue in membering process in HMI Pekanbaru.This research is using qualitative research method with the informant’s selection used purposive technique, with selecting eight chosen informants that is a chairman, two administrators, and five instructors HMI Pekanbaru. The object of research is the activities of instruction communication HMI Pekanbaru to build the regeneration’s personality. The sampling method used observation, interview, and documentation. In tne order to gain the valid data in this research, researcher participate, take part in extension way and triangulation.The result of this research shows personality forming that begin with Basic Training process (LK I). Instruction communication process consist of three phases that is pre-training phase, training, post-training. The most intense communication happens in training phase. The using methode consist of lecture, debarating discussion, brain storming, focus group discussion, demonstration, stimulation, projection or line of duty. The lecture method is the likely method used by instructor. Instructional method is used visual media, audio media, and audiovisual media. The most used media is visual media. The issue of instructional communication consist of psychology issue and technical issue.Keyword : instructional communication, regeneration, HMI